‘French LARS score’: validation of the French version of the low anterior resection syndrome (LARS) score for measuring bowel dysfunction after sphincter-preserving surgery among rectal cancer patients: a study protocol - Rémy Morello; Yassine Eid; Véronique Bouvier; Olivier Dejardin; Benjamin Menahem; Fabien Chaillot; Yannick Chene; Jean Jacques Dutheil; Therese Juul; Arnaud Alves (BMJ Open)
Introduction Many bowel problems following low anterior resection (LAR) for rectal cancer considerably impair the quality of life (QoL) of patients. The LAR syndrome (LARS) scale is a self-report questionnaire to identify and assess bowel dysfunction after rectal cancer surgery. It has been translated and validated in several languages but not in French (metropolitan French). The primary objective is to adapt the LARS scale to the French language (called French-LARS score) and to assess its psychometric properties. Secondary objectives are to assess both the prevalence and severity of LARS and to measure their impact on QoL.Methods and analysis A French multicentre observational cohort study has been designed. The validation study will include translation of the LARS scale following the current international recommendations, assessment of its reliability, convergent and discriminant validities, sensitivity, internal consistency, internal validity and confirmatory analyses. One thousand patients will be enrolled for the analyses. The questionnaire will be initially administered to the first 100 patients to verify the adequacy and degree of comprehension of the questions. Then reproducibility will be investigated by a test–retest procedure in the following 400 patients.An analysis will be conducted to determine the correlation between the LARS score and the Quality of Life Questionnaire (QLQ; European Organization for Treatment and Research of Cancer’s QLQ-C30, QLQ-CR29). Risk factors linked to QoL deterioration will be identified and their impact will be measured. This study will meet the need for a validated tool to improve patient care and QoL.Ethics and dissemination The institutional review board of the University Hospital of Caen and the ethics committee (CPP Nord Ouest I, 25 January 2019) approved the study.Trial registration number NCT03569488.